Uji Efektivitas Peredam Kebisingan Ruangan Dengan Pemanfaatan Limbah Kain Perca Menggunakan Variasi Bentuk Ruang - Anam, Muhamad Khoirul; Pratama, Adi; Lawasi, Muh. Fainal (Virtual of Mechanical Engineering Article, 2019)
Noise becomes a very important issue to reach a level of comfort in the room. Many technical efforts are made to reduce noise levels such as by creating materials that are able to absorb sound waves well. The results of the study show that many materials can be used as noise absorbers, one of which is patchwork waste. The research aim to study is to obtain effective results from room dampening by utilizing used fabric waste. This study examined used fabric waste as soundproof partition walls. The method used to determine the value of sound red uction and absorption coefficient is a method of measuring sound from different positions with variations in fabric types and variations in shape of space. Variations in the type of fabric are woolen fabrics, denim fabrics, and cotton fabrics. While the va riation of the shape of the wake is the shape of a cube, cone and tube. The optimum results obtained at the side measurement position, cube space shape, and type of fabric are wool fabric with a percentage of noise reduction of 35.38% from 80 dB to 51.7 dB .